Towards Future Sustainable Infrastructure: The Role of Technical Audit in Tanzania’s Public Works - Haule, George; Matindana, Juma; Mwaluko, George (Tanzania Journal of Engineering and Technology, 2025)
This study aimed to investigate the vital role and impact of technical audits in promoting sustainable infrastructure development in Tanzania. The role and effects of technical audits in long-term infrastructure development were studied using a mixed-methods approach with both quantitative and qualitative parts. Data were collected through analysis of technical audit documentation, a semi- structured questionnaire, and stakeholder interviews. The study revealed the various dimensions of infrastructure investment projects, including initiation and planning, design, procurement of contractors and consultants, contract management, environment, health, and safety. The technical audit findings reported weaknesses or non- performance issues in infrastructure planning at the national level and in infrastructure projects, programs, and portfolios at various stages of their lifecycle that need to be addressed. The implementation of governance approaches aims to address environmental, social, and economic impacts and achieve investment objectives. The audited entities received recommendations for improvements to address non- performance issues. Furthermore, the timely implementation of these recommendations significantly contributed to the achievement of infrastructure development objectives. Based on the findings, the research concluded that technical audits play a significant role in promoting sustainable infrastructure development in Tanzania. The study recommended strengthening the institutional capacity of organisations overseeing technical audits by investing in training programs, professional development initiatives, and knowledge- sharing platforms. These initiatives will help to improve the technical expertise and competency of auditors and project stakeholders, who will consequently benefit from the technical audit of infrastructure development.